Applicability of robot-assisted laparoscopic radical prostatectomy in renal allograft recipients - Wagener, Nina; Nyarangi-Dix, Joanne; Teber, Dogu; Zeier, Martin; Hohenfellner, Markus (Transplantation proceedings, 2012)
Purpose: To evaluate the general applicability of robotic-assisted laparoscopic radical prostatectomy (RALP) in renal transplant recipients and potential surgical modifications due to the position of the transplanted kidney in the iliac fossa, as RALP has proven to be an effective and safe treatment option for prostate cancer (PCa) removal. Procedures: A 71-year-old patient who had undergone renal transplantation was diagnosed with biopsy-proven localized Gleason 7a PCa. The prostate-specific antigen value was 12.4 ng/mL. RALP was performed by a transperitoneal approach using six ports. By partial mobilization of the bladder, the working space for the radical prostatectomy was created, while leaving the renal transplant and ureter untouched. Lymph node dissection was performed only on the contralateral side of the transplanted kidney. Results: The procedure concluded after 220 minutes and the estimated blood loss was 300 mL. The perioperative clinical course was uneventful. The kidney function remained normal with a creatinine value of 1.2 mg/dL. A complete extirpation of the prostate with negative surgical margins was achieved. After catheter removal, the patient was completely continent. Conclusions: RALP in renal transplant recipients is feasible and can be achieved with favorable oncological and functional outcome. No modifications to the standard RALP technique are required in these patients, except from a partial dissection of the bladder from the abdominal wall and a one-sided lymph node dissection.